Association of CD24, CD27, and co-stimulatory molecules CD80 immunological marker expression on B-cells of human peripheral blood with development of celiac disease - Rahab Abd-Ali Al-Madany; Noor Abdulameer Oudah (Iraqi Journal of Hematology, 2024)
BACKGROUND: B-cells express a variety of clusters of differentiation markers during development. These markers determine the basic function of the immune phenotype specific to B-cells. Changes in the expression of these markers are linked to the development of many diseases, including chronic inflammation, autoimmune diseases, and immunodeficiency. OBJECTIVE: The current study aimed to investigate a change in CD24, CD27, and co-stimulatory molecules CD80 expression on peripheral blood B-cells and the extent of their contribution to celiac disease. MATERIALS AND METHODS: A total of 60 male children, whose ages ranged between 8 and 14 years, participated in this study. Thirty-five were identified as having celiac disease, while the control group comprised 25 children with anti-tissue transglutaminase (TG) (immunoglobulin G [IgG]), anti-tissue TG (IgA), and deamidated gliadin peptide (DGP) IgG levels normal. The frequency CD24, CD27, and CD80 expression were measured by flow cytometry. RESULTS: Celiac disease patients showed a substantial decrease in the percentage of CD24, CD27, and CD80 expression on B-cells compared to control groups. CONCLUSION: These findings suggest that numerical deficiency of CD24, CD27, and CD80 expression on B-cells in the peripheral blood mononuclear cell population, that may involve the loss of auto-tolerance that plays an important role in the immune response associated with inflammation and tissue damage in celiac disease. These immunological markers may be used as diagnostic indicators for this disease.